KONSEP PENATAAN PERMUKIMAN TEPIAN SUNGAI DURI ROXY JAKARTA BARAT - Priyomarsono, Naniek Widayati; Lianto, Fermanto; Mariana, Friska; William, William (Jurnal Bakti Masyarakat Indonesia, 2020)
The rapid development of Jakarta city is sometimes uncontrollable and independent of supervision. Likewise, a series of villages on the banks of the Duri river opposite Roxy Mas, which grow and develop without control, so it looks very vile. The residents of the village series consist of middle to lower class people, with livelihoods; motorcycle taxi drivers, construction workers, vegetable artisans, washermen, porter, and hawkers. This kind of work potential is actually needed by middle and upper class city residents. Problems that arise are the slum neighbourhood that ruin the city view, the danger of fire, the inhabitants of the community are very easily triggered by conflicts that cause quarrels. The method used is qualitative by way of approaching the inhabitants of society by using the theory of Strategy Grounded Theory Research, this is due to the fact that not only physical buildings are studied but also include people who occupy the research area and their culture. Devotion is done in 3 stages ; Stage1. a. Collecting social data by means of in-depth interviews with Focus Group Discussions (FGD), b. Unit measurement of space. c. Check the existence of the balcony above the river and the door to the outside of the unit leading to the balcony. Expected outcomes are in the form of guidelines regarding spatial planning per unit and its balconies. Stage 2; Give examples of healthy units both in terms of material selection, air circulation, color selection. Stage 3; Give examples of a sturdy balcony, beautiful, pleasing to the eye, and colorful painting. Now this is only devotion to stage 1. ABSTRAK: Perkembangan kota Jakarta yang demikian pesat kadang tidak terkendali dan terlepas dari pengawasan. Demikian juga perkampungan deret di tepian sungai Duri di seberang Roxy Mas, yang tumbuh dan berkembang tanpa kendali, sehingga terlihat sangat kumuh. Penghuni dari kampung deret terdiri dari masyarakat golongan menengah ke bawah, dengan mata pencaharian; tukang ojek, tukang bangunan, tukang sayur, tukang cuci, kuli, pedagang asongan. Potensi kerja semacam ini sebenarnya dibutuhkan oleh warga kota kelas menengah ke atas. Permasalahan yang muncul adalah perkampungan deret yang kumuh merusak pemandangan kota, bahaya kebakaran, masyarakat penghuni sangat mudah terpicu konflik yang mengakibatkan pertengkaran. Metoda yang dipakai kualitatif dengan cara pendekatan kepada masyarakat penghuni dengan memakai teori Strategy Grounded Theory Research, hal ini disebabkan karena yang diteliti tidak hanya fisik bangunan saja tetapi termasuk manusia yang menempati lahan penelitian tersebut beserta kulturnya. Pengabdian dilakukan dengan 3 tahapan yaitu; Tahap1. a. Menjaring data sosial dengan cara wawancara mendalam dengan Focus Group Discussion (FGD), b. Pengukuran unit ruang. c. Pengecekan keberadaan balkon yang berada di atas sungai dan pintu ke luar unit menuju balkon. Outcomes yang diharapkan berupa guidelines tentang penataan ruang per unit beserta balkonnya. Tahap 2; Memberikan contoh unit yang sehat baik dari segi pemilihan materialnya, sirkulasi udara, pemilihan terhadap warna. Tahap 3; Memberikan contoh balkon yang kokoh, indah, enak dipandang, serta pengecatan warna warni. Sekarang ini baru dilakukan pengabdian tahap 1.